(untitled) (Altre Modernità, 2014)
As I have argued elsewhere (Mocini 2009; 2011; 2013), emotions play a decisive role in promotional discourse. The power of logical argument may not be sufficient to convince customers. For this reason, writers or speakers usually appeal to the audience’s emotional response to achieve persuasion. Ekman (1999) claims that surprise is one of the basic universal emotions, and only the basic emotions are the real emotions.1 Following DeLancey (1997; 2001) and other researchers (Dickinson 2000; Aikhenvald 2004; Peterson 2010, 2013), we use the term mirativity to refer to the semantic category employed to mark the fact that some information is new or surprising.